2000
DOI: 10.1107/s0108768100002329
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-to-crystal photodimerization of trans-cinnamamides

Abstract: In the crystals of trans-4-methylcinnamamide, C10HT11NO (I), trans-4-chlorocinnamamide, C9H8ClNO (II), trans-3-(2-thienyl)acrylamide, C7H7NOS (III), and trans-cinnamamide, C9H9NO (IV), the shortest intermolecular C...C distances between the C=C double bonds are 3.670 (2), 3.632 (2), 3.762 (3) and 4.120 (2) A, respectively, for the pair of molecules related by a center of symmetry. The structure analysis was also carried out for trans-2-(p-chlorophenyl)-cis4-(p-chlorophenyl)-1-trans-3-diamidocyclobutane, C18H16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…The SCSC transformation was subsequently confirmed by Ohba, via dynamic X-ray diffraction, using the tail-end irradiation technique described by Enkelmann and coworkers [19]. The reaction was found to occur to a relatively low conversion of 4.5%.…”
Section: Cinnamic Acids Cinnamides and Derivativesmentioning
confidence: 92%
See 1 more Smart Citation
“…The SCSC transformation was subsequently confirmed by Ohba, via dynamic X-ray diffraction, using the tail-end irradiation technique described by Enkelmann and coworkers [19]. The reaction was found to occur to a relatively low conversion of 4.5%.…”
Section: Cinnamic Acids Cinnamides and Derivativesmentioning
confidence: 92%
“…reaction pathways) [18]. For instance, in situ monitoring of the course of SCSC reactions has revealed the ability of bonds to form and break and molecules to rotate in solids [19,20]. Second, are the promising materials science and technological applications of solids that undergo such transformations.…”
Section: Significancementioning
confidence: 99%
“…Usually, the efficient dimerization of cinnamamides occurs in the crystalline phase. An example of this is the dimerization of the trans-cinnamamides 178, R = H, that results in (2 + 2)-photodimerization without destruction of the crystalline form 134 . A study of the crystals formed from phthalic acid/trans-cinnamamide (1:2) has shown that the double bonds lie in a criss-cross fashion.…”
Section: A Cinnamic Acid and Its Derivativesmentioning
confidence: 99%
“…Indeed, as Enkelmann and co-workers demonstrated some time ago, a single crystal of cinnamic acid can form a single crystal of its product, α-truxillic acid, if photons in the “tail” of the absorption band (at low photon energies) are used for irradiation. Since this seminal work, many research groups have demonstrated that organic crystals can maintain their crystallinity upon photoirradiation. A detailed summary of organic materials that undergo single crystal to single crystal (SC-to-SC) photoreactions is given by MacGillivray…”
Section: Introductionmentioning
confidence: 99%
“…To this point, studies of SC-to-SC reactions have relied almost solely on X-ray diffraction for monitoring changes. Although single-crystal X-ray diffraction is an extremely powerful technique, it relies on both the reactant and product species being a priori single crystalline in nature; measuring products with increasing degrees of disorder is very difficult from X-ray diffraction analysis alone. Furthermore, X-ray diffraction of a solid solution results in a bulk average pattern, and no precise information regarding the size scales of either phase is generally gained.…”
Section: Introductionmentioning
confidence: 99%